Simultaneous occurrence of C5 vertebral angioma and C5-C6 discopathy and stenosis - case report - Agnieszka Nowacka; Maciej Śniegocki; Wojciech Smuczyński; Kamila Woźniak-Dąbrowska (Kazimierz Wielki University, 2021)
Introduction. Vertebral angioma is a benign tumor of blood vessels. Since they usually do not cause any pain, they are usually diagnosed by accident while diagnosing other conditions within the spine. In case when pain occurs and persists or even intensifies a vertebroplasty should be performed. Case presentation. A 50-year-old patient admitted to the Neurosurgery Department for surgical treatment of C5 vertebral angioma and C5-C6 stenosis and discopathy. In physical examinations on admission: general condition good, back pain at the lower part of the cervical spine, neck pain radiating to the left upper limb, no sensory disturbance. Based on the clinical symptoms and the MRI image, the patient was qualified for simultaneous surgical decompression of C5-C6 stenosis and C5 vertebroplasty. Because of the C5 vertebral angioma shown in MRI, administration of PMMA was performed in a first step, for vascular coagulation and restoration of C5 vertebral strength, and a discectomy with decompression and implantation of cage at C5-C6 level in a second step. After the surgery the patient's condition improved, pain ailments regressed. Conclusion. The decision and choice of vertebral angiomas treatment must be based both on the clinical symptoms and the MRI image. In case of surgical management of simultaneous occurrence of vertebral angioma and discopathy and stenosis, vertebroplasty should be performed first, followed by decompression and cage implantation.